(untitled) (Global Journal of Human-Social Science, 2012)
Women s historic exclusion from political structures and processes is the result of multiple structural functional and personal factors that vary in different social contexts across countries Political empowerment is among the key issues in third world in general and in pakistan in particular Despite the fact that there are 33 reserved seats available in both the national and local bodies or electoral college but due to social and cultural milieu the participation of female is comparatively meager to male The current study is an attempt to analyze those cultural barriers which obstruct female participation and make them disempowered in their political decision making The study is conducted in ramora village where the data is collected from 150 respondents selected through purposive sampling using semistructure interview schedule A quantitative approach is utilized with the help of spss bivariate analysis chi-square lambda gamma and correlation tests in order to analyze data while the discussion is made-up upon the frequency percentage pictorial forms